Excellence Model for Sustainable Convergence in the EU Higher Education - Valentina Mihaela Ghinea; Alina Mihaela Dima; Shahrazad Hadad (Amfiteatru Economic)
The present paper is constituted around the idea of EU sustainable convergence in higher education in the context of Bologna process. Considering the Systems Theory and by using causal loops diagrams, it is brought forth an excellence model whose implementation facilitates the sustainable convergence achievement. The model represents the result of mapping and modelling a possible dynamics of the higher education system. Used in corroboration with a differentiation strategy, it can yield an efficient tool for solving the funding problem, of achieving excellence (within higher education institutions) and also of obtaining sustainable convergence (at the EU level). The implementation of the model provides each higher education institution the possibility of customizing strategic measures conjointly with the freedom of focusing on the core of its competitive advantage. The strength of the differentiation strategy – model dyad consists in fostering the cultural-economic diversity and the enabling of authentic excellence. Reaching sustainable alignment and convergence in EU higher education takes time and concerted efforts. Achieving excellence within each and every higher education unit takes also strategic thinking at their very own level.